Phenotypic correlations between production characteristics in the Huacaya alpaca - Cordero F, Alfonso (2011)
The aim of the present study was to determine phenotypic correlations between body weight of the alpaca at shearing (PCE), greasy fleece weight (PVS), clean fleece weight (PVL), performance of the fibre Andalusia wash (RFL), mean diameter of the fibre (DMF), fibre length (LF), number of loops (NR), incidence of spinal cord fibres (IM), body weight at parturition (PCP) and body weight of calf at birth (PCC). The study considered 185 white Huacaya alpacas, 1 to 7 years old, from the Lachocc Experimental Center of South American Camelids, Universidad Nacional de Huancavelica, in 2007 and 2008. The phenotypic correlations were: PVS-PVL = 0.99, PVS-LF = 0.55, PVS-DMF = 0.52, PVS-PCE = 0.41, PVL-LF = 0.57, PVL-DMF = 0.54, PVL-PCE = 0.43 (p<0.01). Fleece weight does not show any interference with main characteristics related to fibre production, and due to the high interrelation between dirty fleece weight and diameter of fibre, it can be used as a valid criterion for selection in a genetic improvement programme aimed at fibre production.